2019
DOI: 10.1038/s41598-019-51049-4
|View full text |Cite
|
Sign up to set email alerts
|

Osmotically Driven and Detected DNA Translocations

Abstract: A salinity gradient propels a DNA molecule through a solid-state nanopore and generates an ionic current whose change allows for the detection of the translocation. Measurements and theoretical analyses reveal the role of diffusio-osmosis in driving these phenomena: After accounting for known salinity-dependent electrode effects, the measured current change caused by the presence of a DNA molecule inside the nanopore and the DNA translocation speed through it both increase with the magnitude of the applied sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…In previous studies with asymmetric salt concentrations, in addition to an increase in electrophoresis, the role of diffusion‐phoresis and diffusion‐osmosis were also discussed as contributing mechanisms for DNA transport [32]. The work of Wanunu et al.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In previous studies with asymmetric salt concentrations, in addition to an increase in electrophoresis, the role of diffusion‐phoresis and diffusion‐osmosis were also discussed as contributing mechanisms for DNA transport [32]. The work of Wanunu et al.…”
Section: Resultsmentioning
confidence: 99%
“…On the DNA front (under asymmetric salt conditions), Wanunu et al demonstrated a considerable enhancement in DNA capture rate (C R ) and detection of picomolar concentrations of DNA [26]. Sha et al were able to improve the SNR [31] and McMullen et al demonstrated osmotically driven DNA without an external voltage [32]. Interestingly, Zhang et al demonstrated that conductive pulses can be observed under high salt (gradient) conditions by increasing the trans side electrolyte concentration.…”
Section: Abbreviationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several approaches have been verified to face this challenge . Among the various strategies examined, such as active controls by means of adding external forces through light irradiation and gate voltages as well as passive methods via changing viscosity , and temperature of liquid, a salt gradient approach was reported to be useful for manipulating the translocation dynamics through the induced self-built electric field that serves not only to slow down the motions of objects such as DNA and nanoparticles but also to raise the capture rates in the conduit. Meanwhile, the mechanism is predicted to become ineffective in pores of size much larger than the Debye length since it relies on ion-selective transport across the membrane to induce ion concentration polarization via the profound influence of surface charges on the nanopore wall. Despite the fact that such condition is common in nanopore sensing of relatively large particles and molecules such as viruses and amyloids, along with the fact that various intriguing phenomena have been found in resistive pulse sensing using submicrometer channels such as pore shape-dependent ion blockage characteristics, ,, deformations of soft particles, and concentration-polarization-induced ionic current enhancements, , little experimental efforts have been devoted so far to assess the feasibility of the salt gradient approach for controlling the translocation dynamics of non-DNA objects in the non-ion-selective channels.…”
Section: Introductionmentioning
confidence: 99%